Evaluation and Co-Relation of Temporomandibular Disorders Concerning Dental Anomalies in Adolescents and Early Adulthood: Life Sciences -Oral medicine and Radiology - Bhargava, Dr.Pragati; Bhowate, Dr. Rahul (International Journal of Life Science and Pharma Research, 2023)
Temporomandibular joint disorder (TMD) is a complex, multi-factorial etiology. TMDs in the pediatric populationmay go unreported in most cases and can negatively impact their quality of life and their learning ability. To evaluate andcorrelate parafunctional habits in the causation of temporomandibular disorder in adolescents and early adulthood. 340 subjectswith adolescents and early adulthood from 6-18 years were included in the present study. Detailed parameters relevant to TMJdisorder, including the clinical examination findings, were recorded in the structured case sheet. Further, these subjects werecategorized into symptomatic and asymptomatic TMDs. Of the 340 study population, 194 (57%) were identified as suffering fromTMD. A significant difference was recorded in diet practice and oral habits with the patients suffering from TMDs (p<0.05).There was a significant difference in the habits of symptomatic patients. A high prevalence of TMDs in adolescents and earlyadulthood was found in women with bruxism and nail-biting oral habits. Active screening of children with various predisposingfactors is recommended to aid in the early recognition and treatment of TMDs.